2010
DOI: 10.3109/07420528.2010.512992
|View full text |Cite
|
Sign up to set email alerts
|

24-HOUR TEMPORAL PATTERN OF NTPDase AND 5′-NUCLEOTIDASE ENZYMES IN RAT BLOOD SERUM

Abstract: Circadian rhythms represent an important mechanism to prepare the organism for environmental variations. ATP, ADP, AMP, and adenosine can act as extracellular messengers in a range of biological processes and are metabolized by a number of enzymes, including NTPDases and 5'-nucleotidase. In the present study the authors report that ATPase and ADPase activities present 24-h temporal variations that peak during dark (activity) span. These findings suggest that this enzymatic temporal pattern in blood serum might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
2
17
0
1
Order By: Relevance
“…It is interesting to note that a recent study from our group examining a possible temporal variation in the nucleotidases activities found an increase in ATP and ADP hydrolysis in rat blood serum during the dark (activity) phase [12]. During this phase, which is the time of greatest activity in rodents, there is an increase in sympathetic activity compared with the light (rest) phase, and consequently, increased circulating NE.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…It is interesting to note that a recent study from our group examining a possible temporal variation in the nucleotidases activities found an increase in ATP and ADP hydrolysis in rat blood serum during the dark (activity) phase [12]. During this phase, which is the time of greatest activity in rodents, there is an increase in sympathetic activity compared with the light (rest) phase, and consequently, increased circulating NE.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work by our group demonstrated that ATPase and ADPase activities exhibit a circadian temporal pattern in rat blood serum, with the highest enzyme activities during the dark (activity) phase [12]. In contrast, 5′-nucleotidase did not show a temporal pattern.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations